Impact of Corporate Sustainability Performance on Financial Performance of South African Industries Via Brand Value and Competitiveness - OBIOHA, Emmanuel Obinali (International Journal of Environmental, Sustainability, and Social Science, 2024)
Sustainability managers and stakeholders unanimously recognise that a single, systematic and integrated model for measuring corporate sustainability performance significantly enhances firms’ competitive advantage, profit and performance. Nevertheless, serious concerns exist in literature on the non-existence of a single, systematic and integrated model for measuring the impact of corporate sustainability performance (i.e. environmental, social, and economic) on the financial performance of South African industries via brand value/reputation and competitiveness. Thus, the objective is to develop this model by collecting qualitative and quantitative data through a census of 70 out of 74 companies of Johannesburg Stock Exchange, active in Socially Responsible Investment Index. Factor analysis was used for data reduction, Chi-square tested for association between categorical variables, and Cronbach alpha for internal consistency and reliability of instruments. Findings revealed positive impacts between environmental, social and economic aspects of corporate sustainability performance, brand value/reputation, competitiveness and financial performance. Results also showed that the elements/factors of corporate social performance like ethical behaviour, genuine community initiatives and human rights can translate to brand value/reputation. Likewise, elements/factors of brand value/reputation like competitive edge, comparative advantage, innovation, reputation, employees’ loyalty and non-market effect can translate to competitiveness and financial performance. By implication, the model can be useful to potential managers in South Africa or world for making easy and prompt decisions on past, pending and future environmental, social and economic sustainability. Hence, the research contributes to development science a single, systematic and integrated evaluation model adaptable to companies, businesses and governments/municipalities for achieving performance targets.